1999
DOI: 10.2170/jjphysiol.49.283
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Mechanism of Rectal Motility Response Induced by the Epicardial Application of Lactic Acid.

Abstract: The epicardial application of lactic acid induced a biphasic rectal motility response in lightly anaesthetised, open-chested and artificially ventilated cats. This rectal biphasic response is reflexogenic in nature as epicardial lignocaine abolished such response. This rectal biphasic response is abolished by cardiac sympathectomy and reprecipitated by left inferior cardiac afferent nerve stimulation. Such response is also abolished by sacral ventral rhizotomy and reproduced by stimulation of the peripheral cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The butylate-induced contractions were significantly reduced by indomethacin (a PG synthesis inhibitor) and by SC19220, an inhibitor of the excitatory action of PGF 2a , PGE 2 and PGI 2 . Koley et al 21) reported that lactic acid evoked biphasic intrectal pressure changes (i.e. initial relaxation followed by contraction which decays to baseline levels), and the epicardial lactic acid-induced rectal contractile phase was absent in atropinised cats, whereas the relaxation phase was abolished in N G -nitro-L-arginine (nitric oxide blocker) pretreated animals.…”
Section: Resultsmentioning
confidence: 99%
“…The butylate-induced contractions were significantly reduced by indomethacin (a PG synthesis inhibitor) and by SC19220, an inhibitor of the excitatory action of PGF 2a , PGE 2 and PGI 2 . Koley et al 21) reported that lactic acid evoked biphasic intrectal pressure changes (i.e. initial relaxation followed by contraction which decays to baseline levels), and the epicardial lactic acid-induced rectal contractile phase was absent in atropinised cats, whereas the relaxation phase was abolished in N G -nitro-L-arginine (nitric oxide blocker) pretreated animals.…”
Section: Resultsmentioning
confidence: 99%